Dinamika Dagang dan Tasawuf Ekonomi Warga Keturunan Banjar di Tulunggagung - Rusyadi, Refki; ., Fitrianatsany (Universitas Wijaya Kusuma Surabaya, 2024)
This research explains how Banjar ethnic community descent have a character that does not give up easily, has its own patterns and attitudes when interacting with the community and has typical Banjar principles in carrying out economic activities. This research is a type of qualitative research using socio-economic and ethnographic approaches. The result is that the existence of the Banjar society is manifest in the form of religious and trade activities. Spiritual activities in the Al Muhibien community broadcast religion, and the language typical of the Banjar tribe when carrying out activities. Although the Banjar tribe is more identical with gold trading, the Banjar people in Tulungagung place more emphasis on an economy that has religious values and builds branding that the economic principles of the Banjar people are Islamic.Keywords: banjar, diaspora, tribal existence and political economy